Response Surface Optimization of Flexspline based on Parameter Sensitivity - Shijie Chen; Jiahao Li; Baisheng Wu (Jixie chuandong)
The stress concentration effect can be reduced and the fatigue life of flexspline can be improved by reasonably selecting the structural parameters of flexspline. Based on the sensitivity analysis of parameters，the key parameters affecting the stress of the flexspline are screened out. The optimization objectives are to minimize the maximum equivalent stress of the gear ring and the volume of the harmonic reducer in the processes of no load as well as loading， the response surface optimization of flexspline parameters is completed. Through fatigue calculation，it is found that the life of the optimized flexspline is improved to a certain extent.